Experimental investigation on a thermoelectric cooler to evaluate the efficiency of a passive temperature harmonization device - Alles, Akilou; Kpelou, Pali; Mouzou, Essowè; Apedanou, Gagnon Koffi; Kongnine, Damgou Mani (Edelweiss Applied Science and Technology, 2026)
This study evaluated the efficiency of a passive thermal homogenization device (aluminum tube) designed to optimize the temperature profile in a thermoelectric cooler (TEC) box. An experimental approach was considered, comparing a standalone TEC1-12706 Peltier module with a system integrated with an aluminum tube. Both configurations operated under natural convection with passive thermal management on the TEC hot side. The introduction of the aluminum tube led to a temperature reduction of 10°C inside the tube compared to 5°C in the rest of the enclosure, creating two distinct thermal zones. The results showed that the COP value increased from 35% to 250%, with an average gain of 80%, compared to the module without the aluminum tube. Although the absolute Coefficient of Performance (COP) remains lower than that of active systems, the incorporation of the aluminum tube significantly mitigates thermal stratification within the storage medium. These results underscore the potential of this approach for sustainable cooling applications in energy-constrained regions, primarily due to reduced mechanical complexity and enhanced system robustness.